Ramaricium yunnanense sp. nov. (Gomphaceae, Gomphales) from China - Gu, Jin-Ying; Zhao, Chang-Lin (Phytotaxa, 2022)
A new corticioid fungus belonging to Ramaricium is described from China based on morphology and molecular phylogenetic analyses. It is characterized by annual, resupinate basidiomata with a white hymenial surface, a monomitic hyphal system with generative hyphae bearing clamp connections, and ellipsoid to subglobose basidiospores with thin, colorless, ornamented walls. Phylogenetic analyses of combined internal transcribed spacer (ITS) and large subunit nuclear ribosomal RNA gene (nLSU) regions showed that the corticioid fungus is a distinct species in Ramaricium and nested sister to R. polyporoideum. The new corticioid fungus is described and named as Ramaricium yunnanense in this study. A full description, illustration, and a phylogenetic tree to show the placement of Ramaricium yunnanense sp. nov. are provided.